2001
DOI: 10.2337/diabetes.50.2.444
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Stretch and Hypertension Induce Retinal Expression of Vascular Endothelial Growth Factor and Vascular Endothelial Growth Factor Receptor—2

Abstract: A single exposure to 20% symmetric static stretch increased KDR mRNA expression 3.9 ± 1.1-fold after 3 h (P = 0.002), with a gradual return to baseline within 9 h. In contrast, BRECs exposed to cardiac-profile cyclic stretch at 60 cpm continuously accumulated KDR mRNA in a transcriptionally mediated, time-dependent and stretchmagnitude-dependent manner. Exposure to 9% cyclic stretch increased KDR mRNA expression 8.7 ± 2.9-fold (P = 0.011) after 9 h and KDR protein concentration 1.8 ± 0.3-fold (P = 0.005) after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(73 citation statements)
references
References 102 publications
5
64
0
4
Order By: Relevance
“…VEGF is thought to have a central role in increased vascular retinal permeability and in the development of intraocular neovascularization in DR. 31 The fact that retinal pigment epithelial cells respond to stretch by increasing the expression of VEGF was first demonstrated by Seko et al 32 This finding was confirmed and extended by Suzuma et al, 33 who showed that bovine retinal endothelial and pericyte cells exposed to cyclic stretch increase the expression of VEGF and its receptor, both protein and mRNA. Later, it was suggested that stretch-induced retinal VEGF expression was mediated by phosphatidylinositol 3-kinase and protein kinase C. 34 Furthermore, it has been demonstrated that stretch induces apoptosis in porcine retinal pericytes that may be mediated by oxidative stress.…”
Section: In Vitro Studies Searching For the Mechanism Of The Interactmentioning
confidence: 75%
“…VEGF is thought to have a central role in increased vascular retinal permeability and in the development of intraocular neovascularization in DR. 31 The fact that retinal pigment epithelial cells respond to stretch by increasing the expression of VEGF was first demonstrated by Seko et al 32 This finding was confirmed and extended by Suzuma et al, 33 who showed that bovine retinal endothelial and pericyte cells exposed to cyclic stretch increase the expression of VEGF and its receptor, both protein and mRNA. Later, it was suggested that stretch-induced retinal VEGF expression was mediated by phosphatidylinositol 3-kinase and protein kinase C. 34 Furthermore, it has been demonstrated that stretch induces apoptosis in porcine retinal pericytes that may be mediated by oxidative stress.…”
Section: In Vitro Studies Searching For the Mechanism Of The Interactmentioning
confidence: 75%
“…Captopril and atenolol reduced the cumulative risk of microvascular end-points to the same extent, suggesting an effect related to blood pressure lowering rather than properties intrinsic to the agents. Mechanisms proposed for hypertension-induced worsening of DR include endothelial shear stress and stretchrelated release of VEGF from the vessel wall [95], consequent to impaired autoregulation of retinal blood flow with increasing perfusion pressures [9].…”
Section: Treatment Of Hypertension and Diabetic Retinopathymentioning
confidence: 99%
“…Different VEGF ligands have been associated with other mechanical forces; for example, VEGF-A transcripts were elevated in bovine endothelial cells exposed to 9% cyclic stretch of the substrate for 9 h (25). Although the DNA microarrays used in the present study contained oligonucleotide probes for VEGF-A, neither rigorous Affymetrix (Fig.…”
Section: Discussionmentioning
confidence: 99%